Low-cost gel-filled microwell array device for screening marine microbial consortium - Duran, Clelia; Zhang, Shiyi; Yang, Chongyang; Falco, Maria Lorena; Cravo-Laureau, Cristiana; Suzuki-Minakuchi, Chiho; Nojiri, Hideaki; Duran, Robert; Sassa, Fumihiro (Frontiers in Microbiology, 2022)
In order to exploit the microbes present in the environment for their beneficial resources, effective selection and isolation of microbes from environmental samples is essential. In this study, we fabricated a gel-filled microwell array device using resin for microbial culture. The device has an integrated sealing mechanism that enables high-density isolation based on the culture of microorganisms; the device is easily manageable, facilitating observation using bright-field microscopy. This low-cost device made from polymethyl methacrylate (PMMA)/polyethylene terephthalate (PET) has 900 microwells (600 μm × 600 μm × 700 μm) filled with a microbial culture gel medium in glass slide-sized plates. It also has grooves for maintaining the moisture content in the micro-gel. The partition wall between the wells has a highly hydrophobic coating to inhibit microbial migration to neighboring wells and to prevent exchange of liquid substances. After being hermetically sealed, the device can maintain moisture in the agarose gels for 7 days. In the bacterial culture experiment using this device, environmental bacteria were isolated and cultured in individual wells after 3 days. Moreover, the isolated bacteria were then picked up from wells and re-cultured. This device is effective for the first screening of microorganisms from marine environmental samples.